If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = -11x Reorder the terms: -6 + 12x = -11x Solving -6 + 12x = -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -6 + 12x + 11x = -11x + 11x Combine like terms: 12x + 11x = 23x -6 + 23x = -11x + 11x Combine like terms: -11x + 11x = 0 -6 + 23x = 0 Add '6' to each side of the equation. -6 + 6 + 23x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 23x = 0 + 6 23x = 0 + 6 Combine like terms: 0 + 6 = 6 23x = 6 Divide each side by '23'. x = 0.2608695652 Simplifying x = 0.2608695652
| x^2-18x=1.25 | | 4(5x-8)-3(2x-7)= | | 9(9x)=96x | | 8x=(3x^2)-2 | | 7x-3=4x-24 | | (6f-k)= | | 36m^6+12m^4=m^2+0 | | 8r^2+10r-12=0 | | 10x+3=100 | | 5[3(x+4)-2(1-x)]-x-35=14x+65 | | 1.3-5r=7.8 | | 250x^3+128= | | 5y+6y-81=7y+102+66y | | 4a=3a+20 | | fx=(400+20x)(90-1x) | | (3q-8)(-9q+2)(q-2)=0 | | -2x^2=12x-14 | | 5+3*4-8+2*7= | | 2[9(6-5)]= | | (14x+5)(14x+5)=20 | | 2(x+4)+star=16 | | 5f=f+36 | | 5x+5(2x+10)=10x+12 | | 2(x+4)-5x=23 | | 3x+2star+x=x+6 | | 5x-2=-x+7+6 | | 5(y+5)-5y=31 | | -3+sy=17 | | 8x-1x=7x | | 32-(2c+4)=2(c+7)+c | | ax+by+c+2ax-3by+c+by-c= | | 5=(7-2)/3-x |